Astrocyte regulation of extracellular space parameters across the sleep-wake cycle - Sriram, Sandhya; Carstens, Kaira; Dewing, Wayne; Fiacco, Todd A. (Frontiers in Cellular Neuroscience, 2024)
Multiple subfields of neuroscience research are beginning to incorporate astrocytes into current frameworks of understanding overall brain physiology, neuronal circuitry, and disease etiology that underlie sleep and sleep-related disorders. Astrocytes have emerged as a dynamic regulator of neuronal activity through control of extracellular space (ECS) volume and composition, both of which can vary dramatically during different levels of sleep and arousal. Astrocytes are also an attractive target of sleep research due to their prominent role in the glymphatic system, a method by which toxic metabolites generated during wakefulness are cleared away. In this review we assess the literature surrounding glial influences on fluctuations in ECS volume and composition across the sleep-wake cycle. We also examine mechanisms of astrocyte volume regulation in glymphatic solute clearance and their role in sleep and wake states. Overall, findings highlight the importance of astrocytes in sleep and sleep research.